2011
DOI: 10.1186/1749-7922-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Analytical review of 664 cases of penetrating buttock trauma

Abstract: A comprehensive review of data has not yet been provided as penetrating injury to the buttock is not a common condition accounting for 2-3% of all penetrating injuries. The aim of the study is to provide the as yet lacking analytical review of the literature on penetrating trauma to the buttock, with appraisal of characteristics, features, outcomes, and patterns of major injuries. Based on these results we will provide an algorithm. Using a set of terms we searched the databases Pub Med, EMBASE, Cochran, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…It has been reported that total mortality rate of penetrating injuries of buttock 2.9%, stabbing injury mortality rate 3.8% and gunshot injury mortality rate 2.6% in literature. 1,2 In our case, there is no neurologic, vascular or visceral injuries but only stuck in S2 vertebral spinous. Remaining foreign bodies after penetrating injuries occur by firearm, blastic and stab injuries or accidents.…”
Section: Discussionmentioning
confidence: 49%
“…It has been reported that total mortality rate of penetrating injuries of buttock 2.9%, stabbing injury mortality rate 3.8% and gunshot injury mortality rate 2.6% in literature. 1,2 In our case, there is no neurologic, vascular or visceral injuries but only stuck in S2 vertebral spinous. Remaining foreign bodies after penetrating injuries occur by firearm, blastic and stab injuries or accidents.…”
Section: Discussionmentioning
confidence: 49%
“…Surgery, angioembolization or observation could be preferred according to the observed bleeding and abdominal injuries. 2 In 2014, Lunevicius et al, 8 updated the algorithm and recommended evaluation in the following order: general inspection of the patient, controlling the femoral pulse, neurological examination of the lower extremities, examination of urethra and rectum, and then rectoscopy was suggested after the patient became stable. 9 Radiologists recommend contrast-enhanced rectal CT if there is still clinical suspicion of rectal injury despite rectoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, there is a higher mortality from gluteal stab wounds compared with gluteal gunshot wounds. [ 4 ] This may be related to the delayed diagnosis of serious injuries caused by the false sense of security of what appears to be a simple wound. [ 2 ] Penetrating wounds to the buttock can cause serious vascular injuries (gluteal vessels, iliac vessels), nerve damage (the sciatic nerve, gluteal nerve) or pelvic and abdominal visceral injuries, depending on the direction and depth of the wound.…”
Section: Discussionmentioning
confidence: 99%